Mycophenolate mofetil versus azathioprine as a first-line treatment for autoimmune hepatitis: a comparative systematic review and meta-analysis - Amani M. Ali; Mohamed E. Abdelrahim; Aya M. AbdelMagid (BMC Gastroenterology)
Abstract Background Autoimmune hepatitis (AIH) is a chronic progressive inflammatory liver disease of immune-mediated origin, which causes long-term liver inflammation and damage. Traditionally, treatment includes azathioprine (AZA) combined with steroids, but recent studies have highlighted mycophenolate mofetil (MMF) as a potential alternative, particularly for patients who do not respond well to AZA. Aims This study aimed to evaluate the efficacy and safety of MMF versus AZA combined with steroids as first-line treatment for the management of AIH patients. Methods A comprehensive systematic review was conducted using the keywords: mycophenolate mofetil, Cellcept, and autoimmune hepatitis. Studies comparing MMF to AZA combined with steroids in treatment-naïve patients with AIH were included. Efficacy was assessed based on complete biochemical remission (CBR), non-response, and relapse rates. Safety was evaluated on the basis of the incidence of serious adverse effects that led to treatment discontinuation. Statistical analysis included calculation of odds ratios (OR) and 95% confidence intervals (CI). Results Out of 344 search results, four studies met the inclusion criteria, encompassing a total of 512 patients. MMF combined with prednisolone significantly improved both short-term CBR rates (OR, 2.56; 95% CI, 1.18–5.55) and long-term CBR rates (OR, 5.51; 95% CI, 1.7–17.91) compared to AZA combined with prednisolone. Furthermore, MMF treatment was associated with a significantly lower occurrence of serious adverse events (OR, 0.15; 95% CI, 0.07–0.34). Conclusions Compared to AZA-based regimens, MMF-based first-line therapy for AIH appears to be a more promising, effective, and safe treatment option, yielding higher CBR rates and fewer serious adverse events requiring treatment discontinuation.